Industry 4.0: Is Indonesia Ready? - Susilo, Donny (Universitas Negeri Semarang, 2020)
Developed countries are racing to propose new concept of technology revolution that will bring more benefit to human life. In industrial level, the concept of industry 4.0 has been introduced and applied by most developed countries. Meanwhile, the developing countries are preparing themselves to adopt this new concept and increase their competitiveness in the global market. Indonesia is not excluded from this euphoria. However a lack of regional economic study becomes barrier, especially the readiness of Indonesia to adopt industry 4.0 remains a big question. This study aims to provide a descriptive analysis of Indonesia readiness for industry 4.0 based on its economic and information communication and technology (ICT) development at provincial level. Data visualization and regional economic portfolio matrix analysis method were employed to analyze secondary data from various valid and reliable sources. Jakarta, East Java, West Java, Central Java, Riau, Banten, South Sulawesi and East Kalimantan becomes the most promising provinces with gross regional domestic product and ICT development index above average. Meanwhile, North Sumatra has gross regional domestic product above the average but ICT development index below the average. Reversely, provinces like West Sumatra, South Kalimantan, North Sulawesi, West Papua, Bali, Riau Islands, Yogyakarta and North Kalimantan have ICT development index above the average but gross regional domestic product below the average. The other provinces out of those that are already mentioned still need to spend more effort to increase its economic performance and ICT development within their region.